Crosstalk within a brain-breast-bone axis regulates mineral and skeletal metabolism during lactation - Athonvarangkul, Diana; Wysolmerski, John J. (Frontiers in Physiology, 2023)
To support the increased calcium demands for milk production during lactation, a dramatic and reversible physiological response occurs to alter bone and mineral metabolism. This coordinated process involves a brain-breast-bone axis that integrates hormonal signals that allow for adequate calcium delivery to milk yet also protects the maternal skeletal from excessive loss of bone quality or function. Here, we review the current knowledge on the crosstalk between the hypothalamus, mammary gland, and skeleton during lactation. We discuss the rare entity of pregnancy and lactation-associated osteoporosis and consider how the physiology of bone turnover in lactation may impact the pathophysiology of postmenopausal osteoporosis. Further understanding of the regulators of bone loss during lactation, particularly in humans, may provide insights into new therapies for osteoporosis and other diseases of excess bone loss.